2019
DOI: 10.1108/jppel-03-2019-0011
|View full text |Cite
|
Sign up to set email alerts
|

The impact of compensation upon urban village residents satisfaction with the land expropriation process

Abstract: Purpose The purpose of the paper is to investigate compensation and related welfare issues in the case of the expropriation of land for urban redevelopment in China. Design/methodology/approach A mixed methods quantitative and qualitative approach was selected to undertake the research. This involved a wide ranging qualitative review of the academic and policy literature to explore the relevant arguments and issues, combined with a quantitative regression analysis of survey data collected from research subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…When developing homes and making plans for the resettlement community, it must be a key concern to create conditions that meet the needs of MAFs. These findings are consistent with what other research has shown, which is that MAFs are happier at home and have a higher QoL when their house's surroundings are enhanced [15,17,[51][52][53][54].…”
Section: Discussionsupporting
confidence: 93%
“…When developing homes and making plans for the resettlement community, it must be a key concern to create conditions that meet the needs of MAFs. These findings are consistent with what other research has shown, which is that MAFs are happier at home and have a higher QoL when their house's surroundings are enhanced [15,17,[51][52][53][54].…”
Section: Discussionsupporting
confidence: 93%
“…The selection of independent variables was guided by the Andersen's service utilization model ( 29 ), which categorizes predictors of health service utilization into predisposing, enabling, and need factors. In this study, gender (male vs. female), age ( ≤ 30, 31–59, ≥60 years), and marital status (married vs. others) were deemed as predisposing factor, while residency (urban vs. rural), risk level of regions (high vs low), educational attainment (with or without a university degree), personal income (≥average (5,000) vs. < 5,000 Yuan per month ( 33 )), health insurance coverage (yes vs. no), pregnancy or co-habitant with a pregnant woman (yes vs. no), and using Internet medical services (yes vs. no) measured enabling factor. In China, more than 50 accumulative active cases of COVID-19 in a municipality over a period of 14 days would be classified as high risk ( 7 ).…”
Section: Methodsmentioning
confidence: 96%
“…In order to further test the authenticity and credibility of the data, this study used Cronbach reliability analysis method to measure the reliability level of the data. If the coefficient of Cronbach's αS0.7, it indicates that the data reliability is acceptable, and the larger the reliability coefficient value, the better (Feng and Tian, 2011), (Chai et al, 2019). Calculated by SPSS statistics, the coefficient of Cronbach's α of the total amount table was 0.956, which met the standard.…”
Section: Social and Economic Datamentioning
confidence: 95%